Root Canal Irrigants and Dentin Bonding: An Update - Mohammadi, Zahed; Yaripour, Shapour; Shalavi, Sousan; Palazzi, Flavio; Asgary, Saeed (Iranian Endodontic Journal, 2017)
The purpose of the review was to assess the effect of root canal irrigants on dentin bonding. A PubMed-based search was conducted on the articles published from 1980 to 2016. A brief overview and reviewing the effect on dentin bonding of common root canal irrigation solutions such as sodium hypochlorite (NaOCl), chlorhexidine (CHX), ethylenediaminetetraacetic acid (EDTA), mixture of a tetracycline, acid and a detergent (MTAD) and ozone was conducted. Findings showed that, depending on the type of dentin bonding, using NaOCl may decrease, increase or not affect the bond strength. In addition, due to its broad-spectrum matrix metalloproteinase-inhibitoryeffect, CHX as well as MTAD can significantly improve the resin-dentin bondstability. However, the effect of ozone therapy on bond strength was controversial. Keywords: Bond Strength; Chlorhexidine; EDTA; MTAD; Ozone; Sodium Hypochlorite